2021
DOI: 10.1371/journal.pone.0258101
|View full text |Cite
|
Sign up to set email alerts
|

Stress and turnover intention among healthcare workers in Saudi Arabia during the time of COVID-19: Can social support play a role?

Abstract: The turnover intention of healthcare workers is a threat to the competence of health services, especially during COVID-19 time. This study aimed to investigate the association between stress and turnover intention among healthcare workers in Saudi Arabia and whether social support could affect this association. In this cross-sectional study, healthcare workers in primary healthcare centers in Saudi Arabia responded to an online questionnaire assessing their sociodemographic and occupational history, stress lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 21 publications
4
31
1
Order By: Relevance
“…This study found that JS has a significant positive relationship with employee TI, which is also supported by a number of behavior and human resource management scholars, such as [ 30 , 36 , 37 , 38 , 39 , 40 ], who have reported that the recent pandemic has created excessive JS, leading to a series of abnormal reactions and discomforts in the physiology, psychology, and behavior of SMEs employees and ultimately leading to them leaving their jobs. It is noteworthy and interesting to mention that most of these studies were conducted from the Chinese perspective, as the highly concerning country of the pandemic along with big population and fast rising of economy.…”
Section: Discussion Of Findingssupporting
confidence: 72%
See 1 more Smart Citation
“…This study found that JS has a significant positive relationship with employee TI, which is also supported by a number of behavior and human resource management scholars, such as [ 30 , 36 , 37 , 38 , 39 , 40 ], who have reported that the recent pandemic has created excessive JS, leading to a series of abnormal reactions and discomforts in the physiology, psychology, and behavior of SMEs employees and ultimately leading to them leaving their jobs. It is noteworthy and interesting to mention that most of these studies were conducted from the Chinese perspective, as the highly concerning country of the pandemic along with big population and fast rising of economy.…”
Section: Discussion Of Findingssupporting
confidence: 72%
“…The outbreak of COVID-19 has made the unstable performance of SMEs more prominent and has sharply increased the JS of the employees, which in turn has caused them to reconsider their future career plans, leading to TI. A very recent study conducted by Al-Mansour (2021) on Saudi healthcare workers revealed that JS caused by the outbreak of COVID-19 has a significant impact on the TI of front-line Saudi healthcare workers who were considering to change their jobs within the next few months [ 40 ]. Wang et al (2020) reported that the current COVID-19 situation has severely affected Chinese SMEs through demotions, pay decreases, and work related anxiety that has ultimately led to employees’ voluntarily resigning from their jobs [ 30 ].…”
Section: Literature Review Research Hypotheses and Theoretical Frameworkmentioning
confidence: 99%
“…Special attentions should be warranted to cases where healthcare workload increases in various emergencies, such as the current pandemic situation to avoid talent drain. 59 , 60 Our results provided insights for improving the affective commitment among hospital employees.…”
Section: Discussionmentioning
confidence: 72%
“…With increased occupational stress among emergency physicians, it is urgently necessary to identify the pathways by which occupational stress affects turnover intention. Previous studies have mainly explored the pathways from occupational stress to turnover intention in hospital physicians ( 13 , 30 ), nurses ( 31 ), and healthcare workers ( 32 ). Few studies have been conducted among emergency physicians.…”
Section: Introductionmentioning
confidence: 99%